[18F]FDG PET/MRI combined with chest HRCT in early cancer detection: a retrospective study of 3020 asymptomatic subjects - Peng, Liling; Liao, Yi; Zhou, Rui; Zhong, Yan; Jiang, Han; Wang, Jing; Fu, Yu; Xue, Le; Zhang, Xiaohui; Sun, Mingxiang; Feng, Gang; Meng, Zhaoting; et al. (European journal of nuclear medicine and molecular imaging, 2023)
Purpose PET/MRI has become an important medical imaging approach in clinical practice. In this study, we retrospectively investigated the detectability of fluorine-18 ( 18 F)-fluorodeoxyglucose positron emission tomography/magnetic resonance imaging ([ 18 F]FDG PET/MRI) combined with chest computerized tomography (CT) for early cancer in a large cohort of asymptomatic subjects. Methods This study included a total of 3020 asymptomatic subjects who underwent whole-body [ 18 F]FDG PET/MRI and chest HRCT examinations. All subjects received a 2–4-year follow-up for cancer development. Cancer detection rate, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the [ 18 F]FDG PET/MRI with or without chest HRCT were calculated and analyzed. Results Sixty-one subjects were pathologically diagnosed with cancers, among which 59 were correctly detected by [ 18 F]FDG PET/MRI combined with chest HRCT. Of the 59 patients (32 with lung cancer, 9 with breast cancer, 6 with thyroid cancer, 5 with colon cancer, 3 with renal cancer, 1 with prostate cancer, 1 with gastric cancer, 1 with endometrial cancer, and 1 with lymphoma), 54 (91.5%) were at stage 0 or stage I (according to the 8th edition of the tumor-node-metastasis [TNM] staging system), 33 (55.9%) were detected by PET/MRI alone (27 with non-lung cancers and 6 with lung cancer). Cancer detection rate, sensitivity, specificity, PPV, and NPV for PET/MRI combined with chest CT were 2.0%, 96.7%, 99.6%, 83.1%, and 99.9%, respectively. For PET/MRI alone, the metrics were 1.1%, 54.1%, 99.6%, 73.3%, and 99.1%, respectively, and for PET/MRI in non-lung cancers, the metrics were 0.9%, 93.1%, 99.6%, 69.2%, and 99.9%, respectively. Conclusions [ 18 F]FDG PET/MRI holds great promise for the early detection of non-lung cancers, while it seems insufficient for detecting early-stage lung cancers. Chest HRCT can be complementary to whole-body PET/MRI for early cancer detection. Trial registration ChiCTR2200060041. Registered 16 May 2022. Public site: https://www.chictr.org.cn/index.html